A small erythropoietin derived non-hematopoietic peptide reduces cardiac inflammation, attenuates age associated declines in heart function and prolongs healthspan - Winicki, Nolan M.; Nanavati, Alay P.; Morrell, Christopher H.; Moen, Jack M.; Axsom, Jessie E.; Krawczyk, Melissa; Petrashevskaya, Natalia N.; Beyman, Max G.; Ramirez, Christopher; Alfaras, Irene; Mitchell, Sarah J.; Juhaszova, Magdalena; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Aging is associated with increased levels of reactive oxygen species and inflammation that disrupt proteostasis and mitochondrial function and leads to organism-wide frailty later in life. ARA290 (cibinetide), an 11-aa non-hematopoietic peptide sequence within the cardioprotective domain of erythropoietin, mediates tissue protection by reducing inflammation and fibrosis. Age-associated cardiac inflammation is linked to structural and functional changes in the heart, including mitochondrial dysfunction, impaired proteostasis, hypertrophic cardiac remodeling, and contractile dysfunction. Can ARA290 ameliorate these age-associated cardiac changes and the severity of frailty in advanced age? Methods: We conducted an integrated longitudinal (n = 47) and cross-sectional (n = 144) 15 month randomized controlled trial in which 18 month old Fischer 344 x Brown Norway rats were randomly assigned to either receive chronic ARA290 treatment or saline. Serial echocardiography, tail blood pressure and body weight were evaluated repeatedly at 4-month intervals. A frailty index was calculated at the final timepoint (33 months of age). Tissues were harvested at 4-month intervals to define inflammatory markers and left ventricular tissue remodeling. Mitochondrial and myocardial cell health was assessed in isolated left ventricular myocytes. Kaplan-Meier survival curves were established. Mixed ANOVA tests and linear mixed regression analysis were employed to determine the effects of age, treatment and age-treatment interactions. Results: Chronic ARA290 treatment mitigated age-related increases in the cardiac non-myocyte to myocyte ratio, infiltrating leukocytes and monocytes, pro-inflammatory cytokines, total NF-κB and p-NF-κB. Additionally, ARA290 treatment enhanced cardiomyocyte autophagy flux and reduced cellular accumulation of lipofuscin. The cardiomyocyte mitochondrial permeability transition pore response to oxidant stress was desensitized following chronic ARA290 treatment. Concurrently, ARA290 significantly blunted the age-associated elevation in blood pressure and preserved the LV ejection fraction. Finally, ARA290 preserved body weight and significantly reduced other markers of organism-wide frailty at the end of life. Conclusion: Administration of ARA290 reduces cell and tissue inflammation, mitigates structural and functional changes within the cardiovascular system leading to amelioration of frailty and preserved healthspan.